TANTANGAN SUPERVISI PENDIDIKAN DI ERA DIGITAL: PERSEPSI GURU DAN KEPALA SEKOLAH DI SD NEGERI 011 SAMARINDA SEBERANG - Rahmita, Siti; Isnaini, Muhammad (STIT Darul Hijrah Martapura, 2025)
This study aims to analyze the challenges of educational supervision in the digital era based on the perceptions of teachers and principals at SD Negeri 011 Samarinda Seberang. The study uses a qualitative approach with a case study design involving 10 teachers and 1 principal as participants. Data were collected through semi-structured interviews and analyzed using thematic analysis techniques. The results of the study reveal four main challenges: (1) limitations in digital infrastructure in the form of unstable devices and internet networks; (2) a digital competency gap between senior and junior teachers; (3) changes in communication dynamics that have led to feedback becoming more formal and less in-depth; and (4) an increase in teachers' workload due to the demands of technological adaptation. The findings also identified strategies that have begun to be implemented, namely collaborative learning among teachers and a blended supervision model that combines online and offline approaches. The study concluded that the challenges of digital supervision are multidimensional, requiring a holistic approach that includes improving human resource capacity, upgrading infrastructure, and developing adaptive supervision models. The practical implication of this study is the need for policies that support comprehensive digital transformation at the elementary school level.